Pharmacokinetics and Metabolism Research of Shenkang Injection in Rats Based on UHPLC-MS/MS and UHPLC-Q-Orbitrap HRMS - Jiang X; Zhou L; Zuo L; Wang X; Shi Y; Du X; Zhang J; Liu L; Li Z; Xue L; Liu X; Sun Z (Dove Medical Press, 2020)
Xiaofang Jiang,1,* Lin Zhou,2,3,* Lihua Zuo,2,3 Xiaohui Wang,4 Yingying Shi,2,3 Xiangyu Du,5 Jun Zhang,2,3 Liwei Liu,2,3 Zhuolun Li,2,3 Lianping Xue,2,3 Xin Liu,1 Zhi Sun2,3 1Department of Traditional Chinese Medicine, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan Province 450052, People’s Republic of China; 2Department of Pharmacy, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan Province 450052, People’s Republic of China; 3Henan Key Laboratory of Precision Clinical Pharmacy, Zhengzhou, Henan Province 450052, People’s Republic of China; 4Department of Ultrasonography, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan Province 450052, People’s Republic of China; 5School of Basic Medical Science, Henan University, Kaifeng, Henan Province 475001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhi Sun; Lin ZhouDepartment of Pharmacy, The First Affiliated Hospital of Zhengzhou University, No. 1 Jianshe East Road, Erqi District, Zhengzhou 450052, Henan Province, People’s Republic of ChinaTel/Fax +86 371 66862570Email sunzhi2013@163.com; fcczhoul@zzu.edu.cnPurpose: Shenkang injection, a traditional Chinese herbal prescription, had been widely used in renal disease due to its perfect curative effect. In this research, a novel, sensitive, accurate and rapid liquid chromatography-tandem mass spectrometric method was developed to simultaneously detect the seven active ingredients in rat plasma of Shenkang injection and investigate its pharmacokinetic behaviors with metabolism profiling meanwhile.Methods: For accurate pharmacokinetic quantitation, a WATERS ACQUITY UPLC® BEH C18 column was used to perform a separation and acetonitrile-water (0.1% formic acid) was selected as mobile phase for gradient elution with a flow rate of 0.20 mL/min. A heated electrospray ionization with selective reaction monitoring mode was used to monitor the precursor-product ion transitions for all the analytes and IS.Results: They all showed good linearity over a wide concentration range (r> 0.996 3) and the lower limit of quantification (LLOQ) was 0.1– 1.0 ng/mL for analytes. The validation parameters were all within the acceptable limits. Furthermore, for metabolism profiling study, metabolites of the seven ingredients were identified from the rat plasma based on the accurate mass and fragment ions. The metabolic pathways mainly focus on reduction, dehydration and conjugation.Conclusion: This study provided an overview of disposition of Shenkang injection, which is highly instructive for better understanding the effectiveness and toxicity of this drug.Keywords: Shenkang injection, pharmacokinetics, metabolism profiling, UHPLC-MS/MS, UHPLC-Q-orbitrap HRMS